2014
DOI: 10.1111/acer.12574
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Trait Selection for Ethanol Consumption and Withdrawal: Genetic and Transcriptional Network Effects

Abstract: Background Data from C57BL/6J (B6) × DBA/2J (D2) F2 intercrosses (B6×D2 F2), standard and recombinant inbred strains, and heterogeneous stock mice indicate that a reciprocal (or inverse) genetic relationship exists between alcohol consumption and withdrawal severity. Furthermore, some genetic studies have detected reciprocal quantitative trait loci (QTLs) for these traits. We used a novel mouse model developed by simultaneous selection for both high alcohol consumption/low withdrawal and low alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 41 publications
5
51
1
Order By: Relevance
“…We used a bootstrapping procedure comparing average module connectivity to that of random gene groups to confirm network partition accuracy (Langfelder et al, 2011; Metten et al, 2014). This procedure generates Z scores for each module as a measure of quality: >2 is considered moderate and >10 is considered high.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a bootstrapping procedure comparing average module connectivity to that of random gene groups to confirm network partition accuracy (Langfelder et al, 2011; Metten et al, 2014). This procedure generates Z scores for each module as a measure of quality: >2 is considered moderate and >10 is considered high.…”
Section: Resultsmentioning
confidence: 99%
“…Parallel WGCNA (Zhang and Horvath, 2005; Langfelder and Horvath, 2008) were performed similarly to previous work (Iancu et al, 2012; Metten et al, 2014) using the R8B6 and R2D2 datasets. Expression data were first filtered for detection across all samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several studies have implicated the Kcnq family of genes in preclinical rodent alcohol drinking models. Kcnq2 expression was increased in the ventral striatum of mice selectively bred for high alcohol consump tion/low withdrawal severity compared with those bred for low alcohol consumption/high withdrawal severity (Table 2) [84]. Additionally, these authors found that Kcnq2 was a positional candidate within the ciseQTL for alcohol consumption and withdrawal.…”
Section: Preclinical Pharamcogenetic Targets For Treating Alcohol Addmentioning
confidence: 92%
“…For example, Snapc3 was identified as a candidate in volved in ethanol consumption and withdrawal in a recent QTL study using a recombinant panel of BxD mice. 29 Snapc3 encodes a component of the small nuclear RNA (snRNA) activating complex required for the transcription of both RNA polymerase II and III snRNA genes. 30 Interestingly, our list of 28 genes also contains Snapc1, which encodes another component of this com plex potentially highlighting snRNA as an important class of molecules in the regulation of reinforcement.…”
Section: J Psychiatry Neurosci 2016;41(3)mentioning
confidence: 99%